Evaluasi Kebijakan Hukum Pidana dalam Pemberantasan Jaringan Narkoba di Indonesia (International Forum of Researchers and Lecturers, 2025)
This study aims to evaluate the effectiveness of criminal law policies in efforts to eradicate narcotics networks in Indonesia during the 2015-2024 period. The drug problem continues to be a serious threat to national resilience, with increasingly organized crime patterns and utilizing sophisticated technology. This research uses a juridical-empirical approach with a qualitative research method to analyze the implementation of criminal law policies towards eradicating drug networks. Data was obtained through literature study and in-depth interviews with stakeholders in the field of drug law enforcement. The results show that criminal law policy in Indonesia still faces various challenges, including inconsistencies in the application of penalties, limited coordination between institutions, and problems in implementing rehabilitation programs. Factors affecting policy effectiveness include aspects of legislation, law enforcement, public awareness, and international cooperation. This research recommends comprehensive policy reform, increasing the capacity of law enforcement officials, strengthening the rehabilitation system, and optimizing regional and international cooperation in combating drug networks